Neutrophils in ANCA-associated vasculitis: Mechanisms and implications for management - Ge, Shangqing; Zhu, Xingyu; Xu, Qinyao; Wang, Junyan; An, Cheng; Hu, Ying; Yang, Fan; Wang, Xinyi; Yang, Yipin; Chen, Shuwen; Jin, Ruimin; Li, Haiyan; et al. (Frontiers in Pharmacology, 2022)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of systemic autoimmune diseases, which is typified by inflammatory necrosis predominantly affecting the small vessels and often accompanied by positive ANCA. Clinically, AAV primarily includes microscopic polyangiitis (MPA), granulomatosis with polyangiitis (GPA), and eosinophilic granulomatosis with polyangiitis (EGPA). It has been found that in AAV pathogenesis, both innate and adaptive immunity are related to neutrophil function mutually. Many proteins, such as myeloperoxidase (MPO) and proteinase 3 (PR3), in neutrophil cytoplasm lead to the production of proteins such as MPO-ANCA and PR3-ANCA by activating adaptive immunity. In addition, through the process of neutrophil extracellular trap (NET) formation, activation of an alternative complement pathway and the respiratory burst can stimulate the neutrophils close to vascular endothelial cells and will participate the vessel inflammation. This review aims to reveal the potential mechanisms regulating the association between the neutrophils and various types of AAVs and to emphasize the results of recent findings on these interactions. Moreover, multiple underlying signaling pathways involved in the regulation of neutrophils during AAV processes have also been discussed. The ultimate goal of this review is to identify novel biomarkers and therapeutic targets for AAV management in the future.